2020
DOI: 10.1186/s10086-020-01926-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of withdrawal resistance for a screw in hybrid cross-laminated timber

Abstract: The aim of this study was to predict the withdrawal resistance of a screw in hybrid cross-laminated timber (CLT) composed of two types of lamina layers. A theoretical model to predict the withdrawal resistance was developed from the shear mechanism between a screw and the layers in hybrid CLT. The parameters for the developed model were the withdrawal stiffness and strength that occurs when a screw is withdrawn, and the penetration depth of a screw in layers of a wood material. The prediction model was validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…All specimens in this direction showed the splitting failure of the wood layer’s fibers, and the failure only happened around the fasteners. Pang et al [ 61 ] reported the same results. Fasteners in this loading direction (T) demonstrated a higher withdrawal resistance than in the L direction.…”
Section: Resultssupporting
confidence: 61%
“…All specimens in this direction showed the splitting failure of the wood layer’s fibers, and the failure only happened around the fasteners. Pang et al [ 61 ] reported the same results. Fasteners in this loading direction (T) demonstrated a higher withdrawal resistance than in the L direction.…”
Section: Resultssupporting
confidence: 61%
“…In the single-wall model, the closest connector to the rotation point was not reached the yield strength. However, in the single-coupled-panel model, all connectors reached the yield strength when the maximum rotation angle happened, because more displacement (12) happened at the connectors on panel 1 due to the displacement between panel 1 and panel 2 (mm). Thus, the predicted values by the single-coupled-panel model were higher than those by the single-wall model.…”
Section: Comparisons Of Predicted Value With Experimental Datamentioning
confidence: 98%
“…The dimensional stability and thermal conductivity of Ply-lam were better than typical CLT [7][8][9][10]. The structural characteristics of Ply-lam under out-of-plane bending and the withdrawal resistance of screws in Ply-lam was investigated [11,12], but the structural performance for shear walls have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Both timber and plywood were made from the larch (Larix kaempferi Carr.) species, and the air-dry density values were 578.9 and 708.4 kg/m 3 , respectively (Pang et al 2020). The density of wood was calculated from the air-dry weight and air-dry volume at the test moisture content (12 ± 2%) according to BS EN 384.…”
Section: Fire Test Specimenmentioning
confidence: 99%